Implementasi Kebijakan Program Merdeka Belajar (Studi Pada Guru Penggerak di SDN Pisang Candi 4 Kota Malang) - Aisam Aisam; Sulafah Fathin Khannanah; Lita Juniati (Journal on Education, 2022)
Intellectual Property Rights are something that is protected by law. Protection of this mark has been regulated in Law Number 20 of 2016 Concerning Marks and Geographical Indications, Mark owners will obtain legal protection for their trademarks after registering their trademarks with the Directorate General of Intellectual Property. Violation of a registered mark will result in claims for the rights of the owner of the registered mark. Intellectual Property Rights are an exclusive right granted by the state to someone who has created a creation in his possession. The concept of IPR is about the right where the mark will be attached to the owner which is permanent, exclusive, wealth, and the result of human reason. Today's developments also increase consumer satisfaction with goods and/or services, not only in terms of quality but using well-known brands can also be seen from a person's prestige. This study aims to find out how important it is to register the brand name of the product to be commercialized, and to understand the extent of protection that can be provided by the Trademark Law for trademarks that have been registered in Indonesia, and to inform about what legal consequences arise from violations. Trademark Act. The research method used is normative legal research conducted by collecting primary data and secondary data. Data analysis in this study used qualitative data analysis methods